(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This scientific article analyzes the role of intensive technologies in the development of the livestock sector, their types, and their economic, social, and environmental effectiveness. Additionally, the main obstacles encountered in implementing intensive technologies - financial, personnel, infrastructural, and institutional factors - are scientifically examined. Priority tasks and implementation mechanisms to address these issues are proposed.